Uses and Gratifications of Consumers in Social Media Commercial Pages: A Study in Three Facebook Business Pages in Bangladesh (Global Journal of Human-Social Science, 2020)
Social media has become a recognized media platform that connects one-third of the world's population. Facebook is the most popular social media in the world. Facebook offers an easy way for businesses to convey content and messages to their target audience by having an online presence through a commercial page. The article focused on finding out the gratification level of the Facebook business pages customers in Bangladesh. Besides, it also focused on changing the marketing system from the traditional market to commercial Facebook pages in the country. This article also tries to find out the differences between Facebook business pages and traditional marketing & try to predict the future of Facebook business pages based on analyzing the study result. The article is based on U&G theory in the 21st century by Thomas E. Ruggiero. It also uses the market segmentation approach by Philip Kotler. The study conducted in both quantitative and qualitative methods. To collect information, the study uses survey, focus group discussion, and in-depth interview methods. The result of the study shows that customers are the controller of the process of Facebook business pages.
Keywords: social media; facebook business page; traditional marketing; consumer; use